Assessing the performance of commercial farms in England and Wales: Lessons for supporting the sustainable intensification of agriculture. (4th October 2018) - Firbank, Les G.; Elliott, John; Field, Rob H.; Lynch, John Michael; Peach, Will J.; Ramsden, Stephen; Turner, Carla
Abstract: Understanding the trade‐offs between yield, ecosystem services, and other societal benefits is a fundamental prerequisite for the sustainable intensification of agriculture. Here, we develop and test an holistic approach to assessing farm performance across production, social, financial, and environmental dimensions. A longlist of potential indicators was reduced to a smaller subset of Headline Indicators, covering financial performance, levels of food production (standardized in terms of energy content), social characteristics of the farmer (including age, level of education, and degree of business cooperation), hours worked on the farm and provision of public access, and environmental quality (including impacts on climate regulation and water quality). A new index for biodiversity was created and validated, based on land use and management. Data were collected from 59 English and Welsh farms, using a questionnaire structured to be similar to the UK Farm Business Survey. Data were analyzed per farm and per unit area. The main overall variation in Headline Indicators was due to positive relationships between production, profitability and predicted levels of nitrate and GHG emissions, while social variables and biodiversity were generally unrelated to production. Cereal production was associated with relatively low levels of GHG emissions per unit of food production. There were strong differences in indicator profiles between farm types. Such metrics have value in helping understand how best to drive sustainable intensification, especially as it should involve reducing the pollution footprint of food production. Abstract : Here we develop an holistic approach to assessing farm using indicators covering financial performance, food production, social characteristics, and environmental quality (including GHG emissions and a new index of biodiversity). This was applied to 59 farms. There were strong differences in indicator profiles between farm types, and positive relationships between production, profitability and predicted levels of pollution, while social variables and biodiversity were generally unrelated to production.